Do climate services make a difference? A review of evaluation methodologies and practices to assess the value of climate information services for farmers: Implications for Africa - Tall, Arame; Coulibaly, Jeanne Y.; Diop, Moustapha (Elsevier, 2018)
This paper addresses the need for more rigorous evaluation of climate service projects and investments given theexistence of little evidence on the actual value of climate services and the challenges that hamper current eﬀortsto evaluate the impact of climate services for the agricultural community.Based on our in-depth review of existing literature from Africa and around the world, we ﬁnd that rigorousmethods for evaluating climate services span qualitative context-based and quantitative methodological ap-proaches. The few studies that have been conducted so far to determine the value of climate services for farmerswere for initiatives that incorporated in their design an evaluation framework. This highlights the importance of experimentally designing climate service programs for evaluation based on an impact pathway, rather than leaving evaluation as an after-thought. To strengthen the evidence base on the actual value of climate in-formation services, complementary evaluation eﬀorts will need to draw on a combination of qualitative and quantitative approaches, be sensitive to the heterogeneity of user groups, and go beyond the focus on agri-cultural production to include other dimensions of the agricultural system.